Clinical and bacteriological characteristics of Corynebacterium keratitis - Hidenori Inoue; Koji Toriyama; Shinobu Murakami; Hitoshi Miyamoto; Wakako Ikegawa; Yuki Takezawa; Yuri Sakane; Yuko Hara; Atsushi Shiraishi (Journal of Ophthalmic Inflammation and Infection)
Abstract Purpose Corynebacterium species are commensals of human skin and mucous membranes and are recognized as important pathogens in ocular infections. This study investigated the clinical characteristics of Corynebacterium keratitis. Methods We retrospectively reviewed cases of bacterial keratitis in which Corynebacterium species were solely isolated from corneal scraping cultures collected at Ehime University Hospital between January 2010 and February 2024. The clinical findings of Corynebacterium keratitis were divided into two types: adherent and infiltrative, which are defined as adhesion to the corneal surface or stromal infiltration, respectively. Results Of the 232 culture-positive cases of bacterial keratitis, 23 (9.9%) were positive for Corynebacterium species alone. The mean patient age was 60.1 ± 21.0 years, and the cohort included 12 males and 11 females. Adherent type was found in 13 patients (56.5%) and infiltrative type was observed in 10 patients (43.5%). Fluoroquinolone eye drops were used by 14 (60.9%) patients and steroid eye drops by 12 (52.2%). Corynebacterium macginleyi was the most commonly identified species (85.7%). 91% of Corynebacterium isolates were resistant to fluoroquinolones. All of C. macginleyi isolates were fluoroquinolone-resistant, and 93.3% of the isolates were highly resistant (minimal inhibitory concentrations > 32 µg/mL). All cases were treated with frequent antimicrobial eye drops, mainly cephalosporins, and the mean treatment duration was 21.6 days. Although no patient required therapeutic keratoplasty, five adherent types required multiple therapeutic debridements to physically remove the bacteria. Conclusions Corynebacterium keratitis presented as adherent and infiltrative types of lesions. The main characteristics of the patient included the use of fluoroquinolone and steroid eye drops.